2022
DOI: 10.3390/ijerph191711008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Gain-Loss Frame on College Students’ Willingness to Participate in the Individual Low-Carbon Behavior Rewarding System (ILBRS): The Mediating Role of Environmental Risk Perception

Abstract: Since Chinese households account for more than half of the country’s total carbon emissions, efforts focused on consumption will be key to reaching carbon reduction targets. The Individual Low-carbon Behavior Rewarding System (ILBRS) is an emerging mechanism in China that encourages the public to develop a low-carbon lifestyle and it is critical to look for various approaches to enhance the public’s willingness to participate in it. The framing effect has been widely used to study pro-environmental behavior as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In this context, Corral-Verdugo et al (2016) and Steg (2023) recommend a number of strategies to encourage individuals and groups to adopt PEB, such as informing people about the impacts of climate change and how to deal with it through the media. As mentioned earlier, studies show how information about reducing energy consumption can influence individuals' behavior, and this reduction could lead to significant reductions in GHG emissions (e.g., Atchike et al, 2022;Elavarasan et al, 2022;Huang et al, 2022;Jinru et al, 2022;Luo et al, 2023;Qi et al, 2022). These strategies require whole community input: social policies, for example, could help reward PEB at the individual and group levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Corral-Verdugo et al (2016) and Steg (2023) recommend a number of strategies to encourage individuals and groups to adopt PEB, such as informing people about the impacts of climate change and how to deal with it through the media. As mentioned earlier, studies show how information about reducing energy consumption can influence individuals' behavior, and this reduction could lead to significant reductions in GHG emissions (e.g., Atchike et al, 2022;Elavarasan et al, 2022;Huang et al, 2022;Jinru et al, 2022;Luo et al, 2023;Qi et al, 2022). These strategies require whole community input: social policies, for example, could help reward PEB at the individual and group levels.…”
Section: Discussionmentioning
confidence: 99%
“…Government is recognized as the key institution in driving changes in personal behavior. However, as discussed in most studies, monetary incentives may not necessarily promote public low-carbon behaviors [ 51 , 52 ]. To achieve more effective results in current low-carbon lifestyles, such as waste classification and the promotion of new energy vehicles and other low-carbon products [ 53 , 54 ], it may be necessary to devise more flexible policies and accelerate the advancement of low-carbon technology to solve the obstacles to adopting low-carbon behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the results of the 2020 Emissions Gap Report showed that household consumption accounts for approximately two-thirds of global greenhouse gas emissions on average. Relevant statistical data show that household consumption in China accounts for 52% of total national emissions [7]. As the micro-object of carbon emission policy implementation, there is a substantial need to investigate the factors influencing residents' low-carbon behavior (LCB) to effectively stimulate their willingness to engage in carbon emissions and shape low-carbon life skills.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, some existing studies have focused on college students and delved into the factors influencing low-carbon consumption behavior. For example, Qi et al [7] discussed the impact of the gain-loss frame on college students' intention to participate in an individual LCB reward system, and Liu et al [8] explored the role of situational factors in lowcarbon consumption behaviors among college students.…”
Section: Introductionmentioning
confidence: 99%